"Behavior, Metabolic Control and Health-related Quality of Life in Diabetic Patients at Bandar Abbas Diabetic Clinic" - T Aghamollaei; H Eftekhar; D Shojaeizadeh; K Mohammad; M Nakhjavani; F Ghofrani Pour (Tehran University of Medical Sciences, 2003)
Diabetes is a chronic disease of lifelong duration, and its management requires a fundamental change in the patient's lifestyle. The aims of this study were to determine behaviors of diabetic patients in relation to management of their disease, assess metabolic control and health-related quality of life of them. The target population was type 2 diabetic patients and a cross-sectional approach was used. We studied 80 randomly chosen patients. To determine behaviors of patients, data was collected using an interview schedule. Metabolic control was assessed by measuring glycosylated hemoglobin (HBA1c), and health-related quality of life was measured by means of WHOQOL-BREF questionnaire. The majority of patients had good compliance with adherence to the prescribed medicines (65% always and 35%often) and foot care practices (82.5%). However, only 6.3% of them administered self-monitoring blood glucose and 38.8% complied with dietary regimen always. Among smokers, 13.8% stopped smoking after being diagnosed with the disease. The mean HBA1c in the whole patient group was 9.25 ± 1.06 and it ranged from 6.9 to 12.9 and only 2.5% of them had optimum control. The mean rating of health-related quality of life in all scales varied between 55.67 and 63.75(maximum score: 100). The highest rated mean score was for physical health and the lowest was for psychological. It is recommended that every effort be made to initiate and promote behavioral change and improve metabolic control in diabetic patients. To achieve this, an appropriate patient's education program should be planned and future research is needed to reveal determinants of compliance behavior and factors associated with metabolic control and health-related quality of life in diabetic patients.